Review on Big Data Analysis on COVID-19 - Vinay Kailash Upadhyay; Dr. Dinesh Dattatray Patil; Prof. Yogesh Patil (International Journal of Engineering and Management Research, 2022)
Big data analytics is in transforming stage and it will continue to grow and contribute in different area like health. In recent past we have been gone through biggest health issue of the century and it taught us a lesson that in this modern world, technology with relevant data can help to us reduce any human challenge. COVID 19 is that health issue which we faced and suffered a lot. Big data provided us a platform which help us to create an accurate and most trusted data base to analyze, track and tackle this situation. Big data provides an elaborate set of attributes, details of infected patient in very explanatory.